Psychophysical control in modern physical education of students at the university - Limarenko, O.V.; Ponomarev, V.V.; Rakovetskiy, A.I. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to justify and develop the content of psychophysical monitoring in physical education for university students as an innovative approach to the comprehensive management of the physical condition of today’s student population in an educational setting, and to recommend its implementation in practice. Methods and structure of the study. The study was conducted at Siberian Federal University in Krasnoyarsk. The sample size consisted of more than 1,200 first- through third-year students. Over the course of three years, psychophysical testing of students was conducted in the following areas: morphofunctional, psychological, cultural-educational, physical development, stress resistance, and physical education literacy. In total, more than 19 groups were analyzed, encompassing various indicators of the students’ psychophysical condition. The collected data underwent mathematical processing by psychophysical condition categories, was systematized into tabular form, and levels of psychophysical readiness by category were developed, along with an integrated indicator of psychophysical readiness for university students. Results and conclusions. The statistical data collected over three years across 19 blocks for assessing and monitoring students’ psychophysical condition also made it possible to select and establish appropriate blocks for evaluating the psychophysical condition of today’s student population. All of this, taken together, made it possible to develop levels of psychophysical condition (excellent, good, satisfactory, unsatisfactory, and low) in points across the following assessment blocks: morphofunctional, psychological, cultural-educational, physical development, stress resistance, and physical education literacy. A comprehensive indicator for assessing the psychophysical potential of university students was also developed. Such an innovative and comprehensive approach to evaluating the results of physical education for university students contributes to the expansion and modernization of the curricular and target content of the general physical education system for students.